Digital Marketing Strategy Of Independent Record Label In Digital Era (Study Case FFWD Records) (The Indonesian Journal of Business Administration, 2020)
With digital development how we consume music is change, thanks to music platform like Spotify, iTunes, and Joox; we can easily hear our favourite song. This might make it easier for music lovers to listen to their favourite songs. On the other hand, it burdens the record label, like independent record label, because musicians already don't seem to need their service. FFWD Records as one of Indonesia independent label, feel the impact of the digital era with the decline in physical sales. In this study author using external and internal analysis. External analysis is used to determine opportunities and threats from the market, while internal analysis is to determine the strengths and weaknesses of the company itself. The analysis will then continue to the SWOT analysis that is built based on the two analysis earlier. After that, IE Matrix and RACE Framework are used to propose strategies that will be used by FFWD Records. The results of the analysis, the authors propose 3 strategies namely, form a digital marketing team; social media, marketplace, and music platform optimization; and optimizing comment features on all online platforms to get feedback from consumers.Keyword: Digital Era, Digital Marketing, FFWD Records, Indie Label, Music Business.